Deep learning-based hybrid multi-task model for adrenocortical carcinoma segmentation and classification - Datta, Nirjhor; Rashid, Md. Hasanur; Rahman, Samiur; Nodi, Naima Tahsin; Uddin, Moin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.